Bicycle & Pedestrian Safety Action Plan: Systems Plan Addendum - Saia, Nick (City of Manhattan, Kansas, 2022)
The original Bicycle and Pedestrian Systems Plan (BPSP), published in February of 2020, identifies a comprehensive set of improvements necessary to a community where walking and biking are safe, enjoyable, comfortable, and dignified. In the long-term, it will provide a unified and thorough framework for transportation and recreation.
Keywords: Manhattan, Kansas; Bicycle safety; Pedestrian safety